Prelicensure Nursing Students' Reflections on Institutional Response to the 2020 COVID-19 Crisis - Kechinyere C. Iheduru-Anderson; Jo Anne Foley (SAGE Publishing, 2022)
The study aimed to describe how prelicensure student nurses perceive academic support and their institutions' response during the 2020 COVID-19 crisis. The shift to online learning caused by the COVID-19 pandemic disrupted every aspect of higher education, including pre-licensure nursing students. Prelicensure nursing education is one of the most stressful programs in higher education. In a period of great uncertainty, it becomes essential to explore how prelicensure nursing students perceive academic support from their institutions. A qualitative descriptive design was employed for the study. Thematic analysis was used to analyze data obtained from 16 semi-structured interviews. Six themes resulted from the data: Disorganization leading to chaos; technology and technical challenges; stress and frustration; am I prepared to be a nurse?; not having money; mental health matters. This study validates the experiences of nursing students. Students' obstacles during the pandemic should be identified and mitigated to promote learning and academic success.